DEVELOPING KAMISHIBAI (JAPANESE CARD-STORY) MEDIA IN TEACHING SPEAKING - Yuli Puji Astutik; Riski Mulyana (Universitas Muhammadiyah Semarang, 2021)
This study aims at developing and testing the feasibility of Kamishibai media as a learning medium by modifying a story adapted from Berau Folklore East Kalimantan. The research method used in this research was Research and Development (R&D) by adapting ADDIE Model of development which covered several steps namely: Analysis, Design, Development, Implementation, and Evaluation. The result of this research was a learning media namely Kamishibai by modifying it with the story of Berau folklore East Kalimantan. Based on the result of media experts’ validation, it showed that the response was 100%, while the result of material and language quality was 93%. It can be summarized that the developed media can be categorized as “Decent” or suitable to be used as a learning media. Meanwhile, the result of students’ responses towards the media developed was 81.13%. it can be considered positive of the media of Kamishibai (Japanese-Card Story) was feasible and suitable to be applicated as the learning media in speaking